ACCOUNTING FOR ADVERTISING COSTS -DIFFERENCES AND SIMILARITIES BETWEEN THE US GAAP, IAS / IFRS AND THE GERMAN COMMERCIAL CODE - Schreiber, Susanne (Journal of European Economy, 2018)
Advertising costs take on increasing importance. Nevertheless, accounting for these costs still involves many problems. Especially, one of the main problems is whether these costs should be treated as assets placed on the balance sheet, or as expenses appearing on the income statement. This paper reveals that in comparison with IAS/IFRS and German Commercial Code, US standards on accounting for advertising costs implicitly offer more alternative accounting treatments. Regardless of the different goals of US GAAP and IAS/IFRS, on the one hand, and German financial reporting, on the other, this paper sets forth that accounting for advertising costs is always dominated by the principles of conservatism and objectivity. This result can be explained with the agency theory.